FORMULASI HPMC SEBAGAI GELLING AGENT GEL EKSTRAK ETANOL DAUN LEILEM (Clerodendrum minahassae teisjm dan binn.) DAN UJI EFEKTIVITAS ANTIOKSIDAN - Seru, Eufrasia R.; Edy, Hosea J.; Siampa, Jainer P. (PHARMACON, 2021)
ABSTRACTLeilem Leaf Extract (Clerodendrum minahassae teisjm and binn.) which is rich in polyphenols has antioxidant activity that can counteract exposure to free radicals which is one of the factors that can damage cells causing premature aging, skin cancer, decreased immune response, and system disorders. central nervous system. The formulation of this Leilem Leaf ethanol extract gel was used by HPMC as a gelling agent because it is resistant to phenol. The purpose of this study was to determine the gel formula for the ethanol extract of leilem leaves using HPMC as a gelling agent, proving that the gel preparation of the ethanolic extract of leilem leaves had good antioxidant effectiveness and met the requirements of the gel preparation. This type of research is experimental, where the formulation of the ethanol extract of leilem leaf gel was carried out by varying the concentration of HPMC at concentrations of 3%, 5%, and 7% b/v. Leilem Leaf Extraction used maceration method and 96% ethanol solvent was used, then an evaluation was carried out which included organoleptic test, pH test, homogeneity test, dispersion test and adhesion test. Testing the effectiveness of antioxidants using the method (1,1 diphenyl 2 pikhrihydrazil) or DPPH. So it can be concluded that the leilem ethanol extract gel formulation containing 3%, 5%, and 7% HPMC met the requirements of the gel preparation in the evaluation test and which had antioxidant effectiveness, namely leilem leaf ethanol extract with 3% HPMC with an Â of 43,40 mg/L..Keywords: Leilem (Clerodendrum Minahassae Teijsm and Binn.), Gel, Antioxidants.ABSTRAKEkstrak Daun Leilem (Clerodendrum minahassae teisjm dan binn.) yang kaya akan polifenol memiliki aktivitas antioksidan yang dapat menangkal paparan radikal bebas yang merupakan salah satu faktor yang dapat merusak sel sehingga memicu penuaan dini, kanker kulit, penurunan respon imun, dan gangguan sistem saraf pusat. Formulasi gel ekstrak etanol Daun Leilem ini digunakan HPMC sebagai gelling agent karena sifatnya tahan tehadap fenol. Tujuan penelitian ini adalah untuk menentukan formula gel ekstrak etanol daun leilem menggunakan HPMC sebagai gelling agent, membuktikan sediaan gel dari ekstrak etanol daun leilem mempunyai efektivitas antioksidan yang baik dan memenuhi persyaratan sediaan gel. Jenis penelitian ini ialah Eksperimen, dilakukan formulasi gel ekstrak etanol daun leilem dengan memvariasikan konsentrasi HPMC pada konsentrasi 3%, 5%, dan 7% b/v. Ekstraksi Daun Leilem menggunakan metode maserasi dan digunakan pelarut etanol 96%, selanjutnya dilakukan evaluasi yang meliputi uji Organoleptis, uji pH, uji Homogenitas, uji Daya Sebar dan uji Daya Lekat. Pengujian efektivitas antioksidan dengan menggunakan metode (1,1-difenil-2 pikhrihidrazil) atau DPPH. Sehingga dapat disimpulkan formulasi gel ekstrak etanol leilem yang mengandung HPMC 3%, 5%, dan 7% memenuhi persyaratan sediaan gel dalam uji evaluasi dan yang mempunyai efektivitas antioksidan yaitu ekstrak etanol daun leilem dengan HPMC 3% dengan nilai 43,40 mg/L.Kata Kunci : Leilem (Clerodendrum Minahassae Teisjm dan Binn.), Gel, Antioksidan.